(Dys‐)Functions and Potentials of Norms as a Guidance System for Peace Mediators. Issue 4 (20th November 2020) - Holper, Anne; Kirchhoff, Lars
Abstract: Despite substantial efforts to translate normative frameworks for peace mediation into practice, so far even well‐respected norms do not seem to function properly as practical guidance for mediators. The authors argue that there are three basic reasons for this failure: first, a lack of sufficient normative knowledge, making it difficult to determine ground rules that any mediator would be wise to consider; second, a lack of a minimal explicit normative consensus regarding the reference frame of a given mediation, acknowledging all differences; and third, a lack of hands‐on methodology for decision‐making when mediators feel deadlocked in contradictory normative pulls. Working towards the authors' key aim – to close these three gaps or at least narrow them –, this article compiles exemplary building blocks of generic normative knowledge relevant in peace processes, presents a tool for mapping the normative structure and dynamics in a given conflict, and finally introduces a practical dilemma methodology to deal with colliding normative expectations.